A compact energy harvesting multiband rectenna based on metamaterial complementary split ring resonator antenna and modified hybrid junction ring rectifier. Issue 2 (13th November 2019) - Benayad, Ali; Tellache, Mohamed
Abstract: This article presents an improved wireless energy harvesting multiband rectifying antenna. The proposed design is based on an original optimized bidirectional complimentary split ring resonator (CSRR) metamaterial multiband antenna and a modified hybrid junction ring rectifier with four rectifying branches. It harvests the ambient radiofrequency radiations at GSM, 1.8 GHz; UMTS, 2.1 GHz; WiFi, 2.45 GHz; and 4G‐2.6 GHz GSM bands. The created prototypes are printed on a 1.57‐mm‐thickness FR4 substrate and achieve the needed dimensional optimization in both antenna and rectifier. The CSRR antenna accomplished a maximum harvesting realized gain of 2.41, 2.26, 1.58, and 2.69 dB on the aforementioned frequency bands, respectively, 63.75% of antenna size reduction, and 23.62% rectifier size reduction regarding the conventional designs. The hybrid ring junction is used to independently match the subrectifiers at each frequency band. The realized rectenna has been accurately tested in both controlled and outdoor environments, achieving a 67.6% peak efficiency at 1.8 GHz frequency band for an input power level of 10 dBm. It powered up a digital batteryless watch in the outdoor experiment.